POGIL (Process Oriented Guided Inquiry Learning) e-Worksheet to Improve Critical Thinking Skills on Reaction Rate Material - Bella Wahyuning Tyas; Dian Novita (UNIB Press, 2023)
The aims of this research were to obtain the eligibility of the POGIL e-worksheet to improve students' critical thinking skills on reaction rate material in terms of validity, practicality, and effectiveness criteria. The type of research was research and development using the ADDIE development model with three stages, Analyze, Design, and Development. The research was obtain validity from the validation sheet in terms of the eligibility of content, presentation, language, and design getting mode â‰¥ 3 so it was declared valid. Practicality was obtained from a response questionnaire supported by a student activity observation sheet. Overall practicality of the response questionnaire has 89.09% (very practical), while the learner activity observation sheet getting mode = 1. Effectiveness was obtained from the pretest and posttest of critical thinking skills supported by student learning results. The result of the critical thinking skills test got N-gain, 0.929 Interpretation, 0.722 Analysis, 0.694 Evaluation, 0.556 Inference, and 0.933 Explanation and obtained a significance value of 0 in the paired sample t-test so it was concluded there was an increase in students' critical thinking skills in reaction rate material after using POGIL e-worksheet. The learning outcomes test data were analyzed using the Wilcoxon signed rank test has 0 probability value, then it can be concluded there is an increase in student learning outcomes in reaction rate material after using the POGIL e-worksheet. Based on the results of validity, practicality, and effectiveness, the development of the POGIL e-worksheet is feasible.